2014
DOI: 10.1097/nna.0000000000000101
|View full text |Cite
|
Sign up to set email alerts
|

Hourly Rounding to Improve Nursing Responsiveness

Abstract: Objective Synthesize the evidence concerning the effect of hourly rounding programs on patient satisfaction with nursing care, and discuss implications for nurse administrators. Background Patient satisfaction is a key metric that influences both hospital ratings and reimbursement. Studies have suggested that purposeful nursing rounds can improve patient satisfaction but the evidence to date has not been systematically examined. Methods Systematic review of published literature and GRADE analysis of eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
83
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 16 publications
1
83
0
Order By: Relevance
“…The second strand positions rounding as a strategy to optimize skilled nursing surveillance, and as a vehicle for collaboration and sharing of nursing expertise. Underpinning both of these strands of activity is acknowledgement of the link between the delivery of timely and responsive nursing care and patient safety (Mitchell et al, ; Twigg, Myers, Duffield, Giles, & Evans, ). Attention to investigating the nature and impact of these 2 broad forms of rounding highlight that both basic (Alaloul et al, ; Blakley et al, ) and expert nursing care (Catangui & Slark, ) is linked to patient safety and improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second strand positions rounding as a strategy to optimize skilled nursing surveillance, and as a vehicle for collaboration and sharing of nursing expertise. Underpinning both of these strands of activity is acknowledgement of the link between the delivery of timely and responsive nursing care and patient safety (Mitchell et al, ; Twigg, Myers, Duffield, Giles, & Evans, ). Attention to investigating the nature and impact of these 2 broad forms of rounding highlight that both basic (Alaloul et al, ; Blakley et al, ) and expert nursing care (Catangui & Slark, ) is linked to patient safety and improved patient outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…A number of systematic reviews have examined the impact of multidisciplinary rounding on patient satisfaction (Gurses & Xiao, 2006), length of stay (Mercedes, Fairman, Hogan, Thomas, & Slyer, 2015), patient satisfaction (Tan & Lang, 2015), and reduction in call bell use and patient falls (Mant, Dunning, & Hutchinson, 2012; (Mitchell, Lavenberg, Trotta, & Umscheid, 2014). Criticism of the merits of rounding includes the view that it is a return to routinized or thoughtless care (Dix & Braide, 2012) and driven by political whim (Snellink, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…For example, previous work suggests positive outcomes with regard to patient rounding (Mitchell et al . ) while there is limited research with regard to specialling (Dick et al . , Wilkes et al .…”
Section: Discussionmentioning
confidence: 99%
“…Tea et al () identified that nurses who consistently set the standard of excellence in patient care ( n = 13) had four main strategies, and one was knowing and listening to patient needs, which is reflected in the current study as nurses' interest in patients' feelings about their care. Thus, it is vital that healthcare professionals recognise patients may feel vulnerable and feeling cared for and listened to is likely to make a difference to their experience of their hospital stay (Mitchell et al, ). Addressing emotional needs as well as physical needs is central to patients feeling that nurses are concerned about them and they are cared for (Burdick et al, ).…”
Section: Discussionmentioning
confidence: 99%